THE ANALYSIS OF DOCTOR’S PATIENT-CENTERED COMMUNICATION SKILLS EFFICIENCY - Olga Vladimirovna Makarova (Siberian Journal of Life Sciences and Agriculture, 2020)
Background: Find out the efficiency criteria of doctor’s patient-centered communication skills.